Lower Member Amputation in Patient with Total Hip or Knee Arthroplasty - J Passini Sánchez; FJ Pérez Lara; R Marín Moya; H Oliva Muñoz (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
In recent years the incidence of both amputations as total joint replacement surgery of lower limbs has been increased. So it is not rare to fi nd both circumstances in the same patient. We discuss about the technical problem of this eventuality.